The Concept of Purification of The Soul In Al-Ghazali's View Is Related To Inner Peace - Mahatma, Masmuni (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Human life today is often faced with various problems ranging from routine, work stress, economic deficiencies and other life problems. The problem will get bigger if not addressed properly. In Islam, humans are taught to draw closer to Allah so that life's problems do not lead to polytheism. Therefore, the purpose of this research is to analyze Al-Ghazali's concept of purification of the soul (tazkiyatun an-nafs) in relation to inner peace. This study used qualitative research methods. The data collection technique in this research is content analysis research. The results of the study concluded that the concept of purification of Al-Ghazali's soul has three stages, namely takhalli, tahalli and tajali. Eliminating the bad qualities that exist in the soul and filling them with good qualities will have an impact on one's way and attitude in dealing with problems. Strong belief in Allah will make a person have inner peace.